Potential Of Purebred Chicken Egg Shell Waste As Liquid Organic Fertilizer To Promote The Growth Of Tomato Plants (Lycopersicum esculentum Mill) - Shalsa Y. Abudrahman; Sunarto Kadir; Moh. Rivai Nakoe (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Eggshell waste is a type of organic waste produced from egg consumption activities, both in households and the food industry. Liquid Organic Fertilizer from eggshell waste has a real effect on the increase in plant height and many leaves in tomato plants. The formulation of the problem in this study is whether the use of eggshell waste is an alternative to increase the growth of tomato plants and whether there is the most effective concentration on the growth of tomato plants. This study aims to analyze the effectiveness of the use of eggshell waste as liquid organic fertilizer in increasing the growth of tomato plants (Lycopersicum esculentum Mill). The type of research is a true experiment using a Complete Random Design (RAL) with four treatments and five replications. The research sample was 20 tomato plant seedlings sown for 21 days. The data was analyzed using the One Way Anova test with an error rate (?) = 0.05 and continued with Tukey's follow-up test. The results showed that the application of liquid organic fertilizer from eggshell waste for six weeks at the high parameters of plants with concentrations of 0 ml (92.40), 50 ml (96.40), 100 ml (110.20) and 150 ml (119.20) with a value of sig. <0.05 and on the parameters of many leaves with concentrations of 0 ml (264.60), 50 ml (270.80), 100 ml (391.60) and 150 ml (406.60) with sig values. <0.05. The results of Tukey's follow-up test obtained that the most effective concentration was 150 ml (P= >0.05). Liquid organic fertilizer from eggshell waste exerts a significant influence on the growth of tomato plants. It is expected for future researchers to use variable variations.